Mediators of intercellular interactions and histological signs of chronic viral liver disease - P. V. Koroy; A. V. Yagoda; G. I. Gilyazova; I. S. Mukhoramova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To establish interrelation of intercellular interaction mediators with histological changes at chronic viral liver disease.Material and methods. Blood contents of immunoglobulins superfamily and selectin molecules was investigated in 101 patients with chronic viral liver diseases. Scores of ICAM-1, VCAM-1, Е-selectin, L-selectin and the Р-selectin were determined by enzyme-linked immunoassay method and were compared to values of Knodell histological activity index and Desmet fibrosis score as well as to E.M. Brunt hepatic steatosis levels.Results. At chronic viral hepatitis ICAM-1 and selectins blood contents increase whereas in patients with liver cirrhosis elevation of all adhesin levels was marked. Concentration of ICAM-1, VCAM-1, Е-, L-and Р-selectin at chronic viral liver diseases was increased along with increase of severity of inflammation and severity of hepatic fibrosis and had positive correlation with histological activity indexes (HAI) and liver fibrosis. Positive correlation of ICAM-1, VCAM-1 and Е-selectin with degree of liver steatosis was found. Level of immunoglobulin superfamily and selectin molecules were characterized by sufficient accuracy in detection of HAI over 8 points and detection of moderate/severe degree of fibrosis.Conclusions. Association of morphological signs with mediators of intercellular interactions indicates their important role in development and progression of chronic viral liver disease.